2012
DOI: 10.1111/jch.12023
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Blood Pressure Responses to Noncardiovascular Drugs: The Beneficial Role of Ambulatory Blood Pressure Monitoring

Abstract: It has become apparent that noncardiovascular drugs can affect blood pressure (BP) in an off-target manner, either by raising or lowering pressure or by negating the beneficial hypotensive effect of concomitantly prescribed antihypertensives. This paper presents compelling evidence that ambulatory blood pressure monitoring (ABPM) should be used to detect BP effects during the development of noncardiovascular drugs. The requirements for standardizing ABPM to obtain the most information from the least number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Furthermore, phase 2 is an opportune time to evaluate drug-induced off-target BP increases because these studies typically involve patients with the disease or disorder of interest, have more intensive monitoring of vital signs compared with phase 3, and use a wider dose spectrum [6]. Many classes of drugs – from antidepressants to NSAIDs to oncologic therapies – can increase BP via distinct mechanisms ranging from activation of the sympathetic nervous system, salt and water retention to inhibition of vascular endothelial growth factor [14]. For example, a number of prior studies using ABPM with the NSAIDs demonstrated the ability to provide more precise information on the pressor effects of these agents outside of the clinical research environment along or when combined with antihypertensive therapies [1517].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, phase 2 is an opportune time to evaluate drug-induced off-target BP increases because these studies typically involve patients with the disease or disorder of interest, have more intensive monitoring of vital signs compared with phase 3, and use a wider dose spectrum [6]. Many classes of drugs – from antidepressants to NSAIDs to oncologic therapies – can increase BP via distinct mechanisms ranging from activation of the sympathetic nervous system, salt and water retention to inhibition of vascular endothelial growth factor [14]. For example, a number of prior studies using ABPM with the NSAIDs demonstrated the ability to provide more precise information on the pressor effects of these agents outside of the clinical research environment along or when combined with antihypertensive therapies [1517].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of prior studies using ABPM with the NSAIDs demonstrated the ability to provide more precise information on the pressor effects of these agents outside of the clinical research environment along or when combined with antihypertensive therapies [1517]. These earlier trials have led the way for utilizing out-of-office BP monitoring that has affected regulatory advice in drug development as it relates to BP changes [6,14]. …”
Section: Discussionmentioning
confidence: 99%
“…Second, as we have noted previously, “While it is essential that appropriate hardware is employed in clinical trials employing ABPM, it is equally (and arguably more) important that appropriately informative software is employed. ABPM monitoring fulfills its full promise when sophisticated software is employed to collate, interpret, analyze, and electronically transmit data for central hosting and analysis.” This allows maximum use of ABPM data for both screening potential trial participants and evaluating the intervention's therapeutic benefit at the end of the trial.…”
Section: Additional Thoughts On Screening Potential Trial Participantsmentioning
confidence: 98%
“…The Joint UK Societies' commentary is well summarized by their statement that they do not recommend “the use of renal denervation for treatment of resistant hypertension in routine clinical practice,” but they remain “committed to supporting research activity in this field.” The ramifications of their observation that “It is remarkable that to date there is no agreement on the precise anatomy of human sympathetic nerves, and in particular the variation in their trajectories relative to the renal arteries”are also addressed by White and colleagues . Importantly, all expert opinions advocated the employment of ambulatory BP monitoring (ABPM) as an informative methodology likely to mitigate the impact of white‐coat hypertension. Interestingly, three of the papers advocated the use of a sham‐control treatment arm, while Mahfoud and colleagues did not, as discussed below.…”
Section: Recent Noteworthy Publicationsmentioning
confidence: 99%